2016
DOI: 10.1038/srep36619
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of HCV and HIV by microwave: a novel approach for prevention of virus transmission among people who inject drugs

Abstract: Hepatitis C virus (HCV) and human immunodeficiency virus (HIV-1) transmissions among people who inject drugs (PWID) continue to pose a challenging global health problem. Here, we aimed to analyse a universally applicable inactivation procedure, namely microwave irradiation, as a safe and effective method to reduce the risk of viral transmission. The exposure of HCV from different genotypes to microwave irradiation resulted in a significant reduction of viral infectivity. Furthermore, microwave irradiation redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…After computing the pressure field as given in eq. (16) it is shown that the "form factor" W is a function of the dimensionless…”
Section: Numerical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After computing the pressure field as given in eq. (16) it is shown that the "form factor" W is a function of the dimensionless…”
Section: Numerical Calculationsmentioning
confidence: 99%
“…It is observed that under physiological conditions of salinity and acidity, virus capsid assembly requires the presence of genomic material that is oppositely charged to the core proteins 10 . Furthermore, few researchers have focused their research on the possibility of inducing photon-phonon interactions 11 in virions, which are the virus causing infections 12,13,14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, not all institutions have access to large UV lamps, and chemical disinfection may cause significant damage to FFRs or leave hazardous residues [ 19 , 20 ]. Microwaves and heat are known to inactivate viruses and bacteria [ [21] , [22] , [23] , [24] , [25] ], including coronaviruses [ 26 , 27 ], and can be accessible and affordable [ 28 ]; however, heat and humidity may impact the electrostatic charges that confer the high filtration efficiency of the polypropylene filter in N95 FFRs [ [29] , [30] , [31] ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, microwave reduction and sterilization techniques are as efficient as those traditional methods, but they do not compromise polymer packaging, and can be applied even with the medium. 1,2 Microwave-related techniques have received great attention over the last decade, [3][4][5][6][7][8][9][10][11][12] . In the microwave technique, microorganisms undergo non-ionizing electromagnetic radiation, with frequency spectrum ranging from 300 MHz to 300 GHz, respectively with wavelengths from 1 km to 1 mm and energies from 1.24 μeV to 1.24 meV.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave‐related techniques have received great attention over the last decade,. In the microwave technique, microorganisms undergo non‐ionizing electromagnetic radiation, with frequency spectrum ranging from 300 MHz to 300 GHz, respectively with wavelengths from 1 km to 1 mm and energies from 1.24 μeV to 1.24 meV …”
Section: Introductionmentioning
confidence: 99%